GCRV S5 and host EGR1 RNAs form chimeric RNA S5-AGUGA-EGR1: A novel mechanism regulating viral gene expression and host antiviral response - Zeen Shen; Yanling Qi; Yiyang Zhang; Liuyang Li; Zhuo Liu; Xing Zhang; Heying Qian; Min Zhu; Xiaolong Hu; Chengliang Gong (Fish & Shellfish Immunology, 2026)

Ultrasensitive detection of 2-Methylisoborneol and geosmin using a stainless steel wire-graphene-Au@Ag hollow nanoshell-modified SERS probe - Yuting Gong; Yuzhu Li; Min Chen; Anhui Lin; Yanfang Wu; Bingyuan Su; Xiaomei Chen (Analytica Chimica Acta, 2026)

Influence of organic-matter occurrence on hydrocarbon-generation timing in source rocks: Evidence from the Shahejie Formation, Dongying Sag, China - Peng-Yan Du; Jin-Gong Cai; Hui-Min Liu; Qian Chao; Zheng Li; Xu Li; Xue-Jun Wang; Jia-Zong Du; Xiang Zeng (Journal of Asian Earth Sciences, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

Solid-state fermentation of waste herbal medicine residues by a novel rumen-derived probiotic consortium for valorization and microbial-metabolite shifts - Junda Li; Jie Xu; Piao Wei; Hanxuan Gong; Min Tian; Weijie Yan; Caiying Ma; Dmitry Il; Yuxin Yang (Bioresource Technology, 2026)

Multi–frequency (UHF, L, S) scintillation at low latitudes during solar minimum: Scale–dependent irregularity response from multi–instrument observations - Zhaohui Xu; Gang Chen; Yaxian Li; Min Zhang; Zhengwen Xu; Haisheng Zhao; Shouzhi Xie; Yuanlin Jia; Chunxiao Yan; Wanlin Gong (Advances in Space Research, 2026)

Food Pattern, Food Selenium and Environmental Stress Regulating the Urinary Selenium in Tibetan Population - Li Wang; Feifei Li; Chang Kong; Hairong Li; Lijuan Gu; Hongqiang Gong; Linsheng Yang; Binggan Wei; Cangjue Nima; Yangzong Deji; Shengcheng Zhao; Min Guo; et al. (Biological Trace Element Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Di-sulfur-fused-ring incorporated, side chain grafted polyaryl indole anion exchange membranes for electrodialysis desalination - Ning Li; Shoutao Gong; Min Yang; Haiyang Zhang; Omer Javed; Fengxiang Zhang; Gaohong He (Journal of Environmental Chemical Engineering, 2026)

Hepatic Transcriptomics Reveals Sexually Dimorphic Expression of IGF/IGFR Genes Underlying Growth Differences in Spinibarbus hollandi - Sixun Li; Mengmeng Wu; Min Zhang; Zihang Xie; Jie Lai; Lilin Zhan; Ziyan Deng; Guojun Cai; Jian Gong; Chong Han; Qiang Li (Marine Biotechnology, 2026)

Sexually dimorphic expression and hormonal responsiveness of steroidogenic Cyp genes during gonadal differentiation in mandarin fish - Jieming Zhang; Shengyue Lin; Ziyan Deng; Weijian Chen; Guojun Cai; Min Zhang; Lilin Zhan; Chong Han; Jian Gong; Qiang Li (Fish Physiology and Biochemistry, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

3D printed hierarchically porous Na4Fe3(PO4)2(P2O7) cathodes enabling multiscale Na+ transport for high-areal-capacity sodium-ion batteries - Liang Yang; Fei Shao; Min-Peng Li; Mao-Cheng Liu; Cheng-Gong Chang; Yu-Xia Hu (Chemical Engineering Journal, 2026)

Resolving multi-metal encapsulation in coal gasification slag via an integrated activation and selective-separation strategy - Xiaoye Hong; Min Fu; Yanbing Gong; Qiqi Li; Zhe Sun; Yongfeng Zhang; Yinmin Zhang; Xiang He (Chemical Engineering Journal, 2026)

Neurovascular decoupling is associated with altered glymphatic function as assessed by the DTI-ALPS index in patients on dialysis - Wenbo Yang; Lijun Song; Mingan Li; Xiaoyan Bai; Boyan Xu; Min Li; Zhenghan Yang; Tiantian Ma; Yong Gong; Gang Fu; Wenjing Zhao; Jing Zhao; et al. (Brain Imaging and Behavior, 2026)

Alternate straw mulching improves sorghum productivity and profitability via moderating soil temperature and conserving moisture in a hot, drought-prone region - Yuzhang Chen; Xin Liu; Songguo Wu; Wei Mo; Min Li; Xi Liu; Licheng Wang; Rui Li; Lijuan Gong (Field Crops Research, 2026)

Nitrogen enrichment boosts subsoil carbon sequestration by enhancing microbial straw utilization - Zheng-Rong Kan; Muhan Li; Xinyue Wang; Yixuan Luo; Ahmad Latif Virk; Gong Wu; Haishui Yang; Feng-Min Li (Plant and Soil, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Exploration of overlap volumes-based IMRT Rapidplan for cervical cancer patients with the aim of OARs sparing - Minfeng Huang; Changfei Gong; Biaoshui Liu; Yili Wang; Jinghua Zhong; Min Wang; Jun Chi; Li Xinyuan; Ruilian Xie; Chunbo Tang (Physical and Engineering Sciences in Medicine, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Energy production is suppressed by vcircRNA_000048- bom-miR-2753-METTL20 regulatory axis in the BmCPV-infected silkworm, Bombyx mori - Huilin Pang; Yuting Li; Min Zhu; Xinyu Tong; Qunnan Qiu; Liuyang Li; Xiaolong Hu; Chengliang Gong; Yunshan Zhang (Insect Biochemistry and Molecular Biology, 2026)

Development of portable and highly sensitive electrochemical sensor for rapid on-site analysis of levofloxacin residue in pork samples - Xia Cui; Xueqiang Chen; Tianxin Xiao; Xinran Wei; Min Gong; Guanjun Nan; Yunzhe Li; Zhimin Luo; Aiguo Zeng (Food Chemistry, 2026)

Physically-constrained flow learning reveals diurnal submesoscale surface currents from geostationary satellite observations - Xiaosong Ding; Xianqiang He; Hemant Khatri; Jiajia Li; Feng Ye; Hao Li; Min Zhao; Fang Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Rapid water-transporting spongy-like porous polyelectrolyte hydrogel evaporator for high-salinity seawater evaporation - Zihui Wang; Junfeng Li; Yuquan Li; Zhiwei Gong; Ting Lu; Min Xu; Likun Pan (Chemical Engineering Journal, 2026)

Taurine Alleviates Sepsis-Induced Myocardial Injury by Inhibiting NF-κB Pathway-Mediated Inflammation, Mitochondrial Dysfunction, and Apoptosis - Junkai Feng; Ting Ma; Liu Yang; Min Li; Dahai Xiao; Pengxin Gong; Ani Zhao; Pu Li; Linong Yao (Cardiovascular Toxicology, 2026)

Diurnal variation analysis of fluorescence quantum yield during algal blooms based on geostationary ocean color satellite - Min Zhao; Hao Li; Xuan Zhang; Xiaosong Ding; Fang Gong (Marine Pollution Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Prenatal exposure to mixtures of metals and metalloids and risk of spontaneous preterm birth: Critical exposure windows and susceptibility factors - Ruiwei Xu; Yi Zhang; Yingfeng Gao; Le Zhang; Bin Wang; Xiaoqian Jia; Min Xu; Zhiwen Li; Jicheng Gong (Journal of Hazardous Materials, 2026)

Enhanced biosynthesis of 2’-Fucosyllactose in Escherichia coli through α-1,2-fucosyltransferase mining and pathway optimization - Wei Wei; Zehong Zhou; Tiantian Li; Heng Li; Jinsong Gong; Min Jiang; Zhenghong Xu; Jinsong Shi (Systems Microbiology and Biomanufacturing, 2026)

Bioturbation experiment reveals the negative impact of physical damage and shading on the growth of Vallisneria spinulosa S. Z. Yan, a rapidly declining submerged macrophyte in the lower Yangtze region - Min Guo; Zhe Li; Chengfeng Luo; Shaoxia Xia; Yunzhe Huang; Geng Huang; Chenglin Li; Leiqiang Gong; Zonghua Zhang; Yong Mei; Hao Luo; Xiubo Yu; et al. (Hydrobiologia, 2026)

Survey of hard ticks in high-incidence area of Severe Fever with Thrombocytopenia Syndrome in China - Min Wang; Lei Gong; Yujie Wang; Lesheng Zhang; Fengfeng Wang; Qi Wang; Qingyue Li; Xiaohe Ma; Zhiguo Cao; Jiabing Wu (Experimental and Applied Acarology, 2026)

A coral-derived neuropeptide suppresses pentylenetetrazol (PTZ)-induced epileptic seizures and improves recognition memory deficits by modulating NPY-Y1R - Qian Chen; Congshuang Deng; Xiaoshan Huang; Aili Wang; Nan Xu; Kaixun Cao; Min Yang; Shang Li; Qiumin Lu; Guiyi Gong; Simon Ming-Yuen Lee (Archives of Toxicology, 2026)
Epilepsy is a prevalent neurological disorder characterized by recurrent and unprovoked seizures. Despite the availability of anti-epileptic drugs (AEDs), a significant number of patients are still suffering from drug-resistant epilepsy. Neuropeptide Y (NPY) signaling system has emerged as a potential target for the development of anti-epileptic drugs due to its modulation of epileptic activity. In this study, we investigated the therapeutic potential of our previously discovered Scleractinia-derived NPY-like peptide (TpNPY) in seizure disorders. The anticonvulsant effects of TpNPY were evaluated using PTZ-induced seizures in zebrafish and mice in vivo. Furthermore, the underlying molecular mechanisms of TpNPY were assessed using glutamate-induced excitotoxicity models in HT22 mouse hippocampal cells in vitro. Our findings indicated that TpNPY could alleviate PTZ-induced seizure behavior, reduce the expression of seizure-associated immediate-early genes and the production of Reactive Oxygen Species (ROS) in zebrafish. In mice, TpNPY improved seizure behaviors, decreased inflammatory cytokine levels, and ameliorated abnormal glial activation in a PTZ kindling epileptic model. Besides, the administration of TpNPY could attenuate the PTZ-induced anxiety levels and improve recognition memory deficits. Moreover, TpNPY promotes neurogenesis and neural synaptic plasticity through the BDNF/TrkB signaling pathway. Additionally, TpNPY restored cell injury and attenuated oxidative stress in glutamate-challenged HT22 cells through the Nrf2/HO-1 signaling pathway. These results highlight the potential therapeutic efficacy of TpNPY in the treatment of seizures and provide new insights into the development of coral-derived anti-epileptic peptide-based drugs.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A plasma membrane receptor complex mediates early heat-responsive signaling to trigger nuclear transcriptomic reprogramming in Arabidopsis - Jing Li; Shifeng Wu; Kun Wang; Yang Xu; Xiaoyan Zhang; Xinru Li; Wen Song; Jian-Min Zhou; Zhizhong Gong; Shuhua Yang; Yanglin Ding (Molecular Plant, 2025)

Simultaneous enhancement of phosphorus release of cell and EPS by carbon source to improve biofilm phosphorus recovery concentration: Performance and mechanism - Ruijing Wu; Min Ni; Yujie Zhang; Huijing Gu; Jiahui Gong; Wenyi Shen; Yong Huang; Yanyan Ding; Lu Li; Yang Pan (Journal of Environmental Chemical Engineering, 2025)

Ln-MOF based magnetic composite nanosensor for sensitive dual-mode fluorescence/colorimetric detection of fluoroquinolones - Fukai Li; Jian Zhou; Kai Li; Min Wang; Mengrui Yang; Ping Gong; Liang Li (Food Chemistry, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

The role of mineral mediation in organic carbon preservation and phosphorus removal in saline lake sediments of the Tibetan Plateau - Dongli Li; Haicheng Wei; Yafei Zou; Xu Wang; Qian Bao; Ronglei Duan; Xiaoyu Gong; Jingfu Wang; Haiquan Yang; Min Zhao; Songtao Li; Haibo He (Journal of Hydrology, 2025)

Magmatic system beneath the Lengshuikeng deposit, South China: Insights from melt inclusions and magnetotelluric inversion of electrical structure - Xue-Jing Gong; Shuai Ruan; Li-Min Zhou; Yong-Peng Ouyang; Leonid Danyushevsky (Journal of Asian Earth Sciences, 2025)

Rapid detection of duck egg ovalbumin (D-OVA) in surimi via fluorescent immunochromatographic assay utilizing shark-derived single-domain antibody - Zhong-Lin Li; Ling-Jing Zhang; Kai-Yuan Cao; Jian-Lian Huang; Chang-Gong Zhang; Le-Chang Sun; Yu-Lei Chen; Min-Jie Cao (Food Chemistry, 2025)

MAO-A inhibition alleviates sepsis-driven lung injury via Nrf2/HO-1 pathway activation and suppression of pyroptosis - Min Li; Hu Li; Liming Gong; Xinmin Chen; Jincan Dai; Jirong Tian; Xiaochuan Yin; Qinghe Yu (Journal of Molecular Histology, 2025)

Assessment of potentially toxic elements (PTEs) in surface and groundwater of volcanic and granite regions of Hainan Island, China: Pollution status, sources, and health risk evaluation - Jianzhou Yang; Yong Li; Shengyue Liang; Min Zhang; Jingjing Gong; Yufang Li; Qiankun Yan; Xiaohui Sun; Zuyang Xu; Xueju Liu; Shuqi Hu; Jianweng Gao; et al. (Environmental Geochemistry and Health, 2025)

Investigation of an Accelerated Deterioration Method for Subsea Tunnel RC Linings via Electromigration and Its Associated Test Parameters - Jiguo Liu; Qinglong Cui; Shengbin Zhang; Xin Li; Longhai Wei; Huimin Gong; Yiguo Xue; Min Han (Journal of Marine Science and Engineering, 2025)
Appropriate accelerated deterioration methods are crucial for studying the deterioration behavior of reinforced concrete linings in subsea tunnels. To investigate the deterioration mechanisms of reinforced concrete (RC) structures in marine environments, this study employed the electromigration method to simulate accelerated chloride-induced corrosion of steel reinforcement. The results demonstrate that under a direct current (DC) electric field, chloride ions migrate directionally and accumulate on the side of the steel facing the chloride source, successfully inducing non-uniform corrosion features that closely resemble those in natural environments. The side facing chloride ingress exhibited severe corrosion and significant cross-sectional loss, while the shielded side remained largely intact. The experimental process clearly reveals that the applied electric field does not directly initiate corrosion of the steel reinforcement before chloride ions migrate to its surface. Furthermore, analysis of experimental parameters showed that symmetrical perforations on electrode plates are crucial for a uniform electric field, while perforation ratio and electrode–specimen distance have a minor influence. The average chloride penetration depths corresponding to electrode plate perforation areas of 5.5%, 15%, 25.5%, and 38.1% were measured as 1.63 cm, 1.67 cm, 1.57 cm, and 1.57 cm, respectively. This research confirms electromigration as an efficient and reliable technique for accelerated corrosion testing, providing a significant theoretical basis for assessing and predicting the long-term durability of marine engineering structures.

A novel method for distinguishing different algal blooms in the East China Sea via geostationary ocean color satellite observations - Min Zhao; Hao Li; Xuan Zhang; Xiaosong Ding; Fang Gong (Frontiers in Marine Science, 2025)
Introduction Dinoflagellate and diatom blooms are the most frequent marine ecological disasters in the Yangtze River estuary (YRE) and adjacent areas of the East China Sea (ECS). Distinguishing between these bloom types is essential for accurate monitoring and effective mitigation. Methods To investigate the physiological differences between bloom types, algal culture experiments were conducted to quantify variations in fluorescence quantum yield (φ) between dinoflagellates and diatoms during the growth phase. Using insights from the experiments, an identification and classification method for harmful algal blooms (HABs) was developed based on Geostationary Ocean Color Imager-II (GOCI-II) data. The method incorporates the difference in remote sensing reflectance (Rrs) between the fluorescence peak and baseline bands and establishes a φ-based classification threshold. Results Validation of GOCI-II Level-2 products showed that fluorescence-band Rrs products have high accuracy and strong correlation with in situ measurements. A threshold of φ = 0.014 was proposed to distinguish dinoflagellate from diatom blooms. The derived methods were successfully applied to GOCI-II imagery, enabling precise detection and classification of HABs in ECS waters. Discussion The proposed approach demonstrated strong capability for monitoring the spatial distribution and evolution of HABs. It provides a reliable technique for distinguishing bloom types using geostationary satellite data, offering valuable support for marine environmental management and mitigation efforts.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isotopic disequilibrium of the retro-diffusive CO2 efflux affects photosynthetic C18OO discrimination and the estimation of mesophyll conductance - Sui Min Huang; Jérôme Ogée; Xiao Ying Gong; Wei Ting Ma; Lei Li; Xuming Wang; Hans Schnyder; Rudi Schäufele (Agricultural and Forest Meteorology, 2025)

A Review on Development, Challenges, and Future Perspectives of Ensemble Forecast - Jing Chen; Yuejian Zhu; Wansuo Duan; Xiefei Zhi; Jinzhong Min; Xiaoli Li; Guo Deng; Huiling Yuan; Jie Feng; Jun Du; Qiaoping Li; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Mechanism of hypoxia tolerance improvement in hybrid fish Hefang bream - Ming Wen; Chunchun Zhu; Yuhua Tang; Hong Zhang; Zheng Liu; Siyu Wang; Min Tao; Li Hu; Wenting Rao; Shengnan Li; Dingbing Gong; Shi Wang; et al. (Aquaculture, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

circEgg inhibits BmCPV infection by regulating the transition between H3K9me3 and H3K9ac - Qunnan Qiu; Xinyu Tong; Min Zhu; Zhe Liu; Mei Yin; Shutong Jiang; Liuyang Li; Yuqing Huang; Yongjie Feng; Xiaolong Hu; Chengliang Gong (Pesticide Biochemistry and Physiology, 2025)

Self-powered ammonia gas sensor based on Ga2O3/Mo2Ti2AlC3 nanocomposite material for environmental monitoring in chicken farms - Mingkai Ma; Zhengkai Li; Weihao Zhu; Min Ju; Likun Gong (Chemical Engineering Journal, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Regulating perovskite/PCBM interface for highly efficient and stable inverted perovskite solar cells - Wei-Min Gu; Mingming Zhao; Qing Wang; Kun Gong; Xuli Li; Yan Sun; Shaojing Sun; Guang Yang; Chunming Hu; Ke-Jian Jiang (Chemical Engineering Journal, 2025)

White matter integrity mediated the effect of plasma uric acid levels on cognitive function in ALS patients - Jiahui Tang; Yali Zhao; Yu Chen; Yuan Yang; Zhenxiang Gong; Zehui Li; Min Zhang; Jing Zhang (Brain Imaging and Behavior, 2025)

Combining modelling and experiment to quantify light interception and inter row variability on intercropped soybean in strip intercropping - Yushan Wu; Meng Chen; Sirong Huang; Yue Li; Min Li; Di He; Pengcheng Hu; Tao Duan; Wanzhuo Gong; Yanhong Yan; Titriku John Kwame; Muhammad Ali Raza; et al. (European Journal of Agronomy, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Gypenoside GP5 effectively controls Colletotrichum gloeosporioides, an anthracnose fungus, by activating autophagy - Yujie Liu; Xinyv Li; Chu Gong; Yonghong Cao; Jun Wang; Min Han; Jun-Li Yang (Postharvest Biology and Technology, 2025)

Optimized carbonylation treatment of Litopenaeus vannamei matrix decreased its immunoreactivity and improved edible quality, simultaneously - Meng Liu; Ming-Xuan Wu; Fei-Fei Gong; Zhao-Min Sun; Ying Li; Fei Huan; Gui-Xia Chen; Qing-Mei Liu; Hong Liu; Guang-Ming Liu (Food Chemistry, 2025)

Glycogen-accumulating organisms promote phosphate recovery from wastewater by pilot-scale biofilm sequencing batch reactor: Performance and mechanism - Min Ni; Yang Pan; Jiahui Gong; Zhiqiang Chen; Dapeng Li; Yong Huang; Lu Li; Yanyan Ding; Zhen Bi (Bioresource Technology, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Au@Ag hollow nanoshells-based SERS integrated microfluidic chip as a sample-to-answer platform for the ultra-sensitive detection of geosmin - Yuting Gong; Dong Li; Min Chen; Anhui Lin; Quansheng Chen; Xiaomei Chen (Analytica Chimica Acta, 2025)

Optimization of relief hole blasting satisfying synergistic constraints of rock-breaking area and hole-bottom minimum burden - Haojun Wu; Jiayin Jia; Min Gong; Jiuhong Li; Sijie Wang; Xinxiang Zhao (Tunnelling and Underground Space Technology, 2024)

Elevated pCO2 may increase the edible safety risk of clams exposed to toxic Alexandrium spp. - Min Pang; Yuchen Gong; Hongju Chen; Ying Shi; Zhao Li; Xiuping He; Junhui Chen; Xuexi Tang; Zongling Wang; Xuelei Zhang; Pei Qu (Science of The Total Environment, 2024)

Atmospheric correction of geostationary ocean color imager data over turbid coastal waters under high solar zenith angles - Hao Li; Xianqiang He; Palanisamy Shanmugam; Yan Bai; Xuchen Jin; Zhihong Wang; Yifan Zhang; Difeng wang; Fang Gong; Min Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Grass Carp Reovirus (GCRV) infection activates the PERK-eIF2α pathway to promote the viral replication - Zeen Shen; Yanling Qi; Wenbin Yu; Song Li; Zhuo Liu; Liuyang Li; Min Zhu; Chengliang Gong; Xiaolong Hu (Fish & Shellfish Immunology, 2024)

Cellulose aerogel evaporators with vertical channels inspired by lotus rods for highly efficient solar water evaporation - Zihui Wang; Fanyue Meng; Xinjuan Liu; Zhiwei Gong; Yuquan Li; Ting Lu; Yefeng Yao; Min Xu; Likun Pan (Desalination, 2024)

Preparation of amino-functionalized CoAl-LDH/palygorskite hierarchical composites for CO2 capture - Shixiang Zuo; Min Sun; Weifeng Gong; Tongtong Tang; Xuhua Ye; Wenjie Liu; Ngie Hing Wong; Rong Xu; Guihua Chen; Chao Yao; Haoguan Gui; Xiazhang Li (Applied Clay Science, 2024)

Assessment of GOCI-II satellite remote sensing products in Lake Taihu - Min Zhao; Huaming Li; Hao Li; Xuan Zhang; Xiaosong Ding; Fang Gong (Frontiers in Marine Science, 2024)
Introduction The Geostationary Ocean Color Imager-II (GOCI-II), launched on February 19, 2020, offers increased observation times throughout the day and higher spatial resolution compared to its predecessor, the Geostationary Ocean Color Imager (GOCI), launched in 2010. To ensure the reliability of GOCI-II data for practical applications, the accuracy of remote sensing products needs to be validated. This study uses in situ data from Lake Taihu for validation. Methods We assessed the accuracy of GOCI-II remote sensing products, including remote sensing reflectance derived using two atmospheric correction algorithms: ultraviolet (UV) and near-infrared (NIR). The study also evaluated the accuracy of derived parameters, such as chlorophyll-a (Chl-a) concentration, total suspended matter (TSM) concentration, and phytoplankton absorption coefficient (a ph ), based on these atmospheric correction algorithms. In situ measurements from Lake Taihu were used as ground truth data for validation. Results Our results revealed that the UV atmospheric correction algorithm provided higher accuracy in Lake Taihu compared to the NIR algorithm. The average absolute percentage deviations (APDs) for remote sensing reflectance across different bands were: 25.17% (412 nm), 29.69% (443 nm), 22.27% (490 nm), 19.38% (555 nm), 36.83% (660 nm), and 33.0% (680 nm). Compared to NIR-derived products, the UV algorithm showed improved accuracy for Chl-a concentration, TSM concentration, and a ph , with reductions in APD values by 16.92%, 3.32%, and 10.91%, respectively. When applying UV correction, the 412 nm band performed better than the 380 nm band, likely due to a lower signal-to-noise ratio at 380 nm and smaller extrapolation errors at 412 nm. Discussion While the NIR algorithm is suitable for open ocean waters, the UV algorithm demonstrated higher accuracy in turbid environments such as Lake Taihu. Therefore, a combined UV-NIR atmospheric correction algorithm may be more effective for handling various types of water environments. Additionally, further research is needed to develop more suitable retrieval algorithms for Chl-a concentration and aph in eutrophic waters to improve accuracy.

Induced resistance to control postharvest stem-end rot by methyl jasmonate in mango fruit - Min Li; Xiangxiang Qu; Deqiang Gong; Tianyu Huang; Yu Wang; Yi Yang; Zhaoyin Gao; Zhengke Zhang; Jinhua Sun; Meijiao Hu (Physiological and Molecular Plant Pathology, 2024)

γ-Aminobutyric acid enhances resistance in postharvest mango fruits to Colletotrichum gloeosporioides by activating related defense mechanisms - Yezhen Chen; Deqiang Gong; Min Li; Zhaoyin Gao; Jinhua Sun; Yi Yang; He Zhang; Yonggui Pan; Zhengke Zhang; Meijiao Hu (Physiological and Molecular Plant Pathology, 2024)

An Eco-friendly β-cyclodextrin/Stilbene-Integrated supramolecular material Realizes the effective treatment of bacterial diseases via enhancing the biofilm eradication and Agrochemical bioavailability - Li Zhou; Yazhen Chen; Jinghan Yang; Yaling Duan; Huiqin Gong; Haojie Ye; Ya Hong; Min Liu; Gefei Hao; Fengpei Du; Peiyi Wang (Chemical Engineering Journal, 2024)

Whole-brain Mapping of Inputs and Outputs of Specific Orbitofrontal Cortical Neurons in Mice - Yijie Zhang; Wen Zhang; Lizhao Wang; Dechen Liu; Taorong Xie; Ziwei Le; Xiangning Li; Hui Gong; Xiao-Hong Xu; Min Xu; Haishan Yao (Neuroscience Bulletin, 2024)

Protective effect of sulforaphane against depressive behavior in mice through glucocorticoid receptor antagonism - Jia Yu; Min Guo; Yiyao Gong; Yijing Yang; Jie Zhang; Li Ren (Food Bioscience, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Ionic liquid-reinforced transparent, stretchable, conductive organic ionic gel with ultra-high sensory capability and ultra-robust impact-resistance - Zhentao Zhang; Min Sang; Yucheng Pan; Zimu Li; Shuai Liu; Jianpeng Wu; Xinyi Wang; Shilong Duan; Xinglong Gong (Chemical Engineering Journal, 2024)

Seasonal and soil compartmental responses of soil microbes of Gymnocarpos przewalskii in a hyperarid desert - Min Li; Chao He; Feng Gong; Xiangyun Zhou; Kehan Wang; Xinrong Yang; Xueli He (Applied Soil Ecology, 2024)

Integrating intrinsic and configural superiority into advanced impact-resistant organohydrogels via cryo-assisted direct ink writing - Shuai Liu; Sheng Wang; Min Sang; Zimu Li; Jianyu Zhou; Junshuo Zhang; Xinglong Gong (Chemical Engineering Journal, 2024)

Biochar-derived dissolved organic matter enhanced the release of residual ciprofloxacin from the soil solid phase - Guo Chen; Jing Ma; Gang Yang; Chao Chen; Lulu Long; Linling Li; Li Gong; Min Xu; Jun Wu; Chun Song; Jiejie Lyu (Chemosphere, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

circ_0000337 Promotes the Progression of Cervical Cancer by miR-155-5p/RAB3B Axis - Jiqin Xu; Bai Xue; Min Gong; Ling Ling; Sipei Nie; Fujun Li; Meixia Wang; Miao Fang; Chen Chen; Qiaoling Liu; Yun Han (Biochemical Genetics, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Distribution and influencing factors of atmospheric nitrogen oxides (NOx) over the east coast of China in spring: Indication of the sea as a sink of the atmospheric NOx - Ye Tian; Hui-Min Jian; Chun-Ying Liu; Jiang-Chen Gong; Pei-Feng Li; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)

In-situ high-speed 3D-DIC experiment on blast-induced second free surface characteristics at initial stage of cut blasting in a tunnel - Haojun Wu; Min Gong; Zhenyang Cao; Xiaodong Wu; Shenglin Li; Xiangdong Meng (Tunnelling and Underground Space Technology, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Correlations between flavor and fermentation days and changes in quality-related physiochemical characteristics of fermented Aurantii Fructus - Ya-Ting Xie; Ting-Ting Bai; Tao Zhang; Peng Zheng; Min Huang; Li Xin; Wen-Hui Gong; Abid Naeem; Fang-You Chen; Hua Zhang; Jin-Lian Zhang (Food Chemistry, 2023)

Identification and functional analysis of myeloid differentiation factor 88 (MyD88) in early development of Haliotis diversicolor - Xiaoting Gong; Min Li; Lili Zhang; Shiyu Huang; Guodong Wang (Fish & Shellfish Immunology, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Ethanol Causes Cell Death and Neuronal Differentiation Defect During Initial Neurogenesis of the Neural Retina by Disrupting Calcium Signaling in Human Retinal Organoids - Yu Gong; Lingling Ge; Qiyou Li; Jing Gong; Min Chen; Hui Gao; Jiahui Kang; Ting Yu; Jiawen Li; Haiwei Xu (Stem Cell Reviews and Reports, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Spatio-temporal prediction of regional land subsidence via ConvLSTM - Jing Leng; Mingliang Gao; Huili Gong; Beibei Chen; Chaofan Zhou; Min Shi; Zheng Chen; Xiang Li (Journal of Geographical Sciences, 2023)

Heterologous expression, fermentation strategies and molecular modification of collagen for versatile applications - Zhi-Xiang Xiang; Jin-Song Gong; Heng Li; Wei-Ting Shi; Min Jiang; Zheng-Hong Xu; Jin-Song Shi (Critical Reviews in Food Science and Nutrition, 2023)

Pressure transient analysis for multi-stage fractured horizontal wells considering threshold pressure gradient and stress sensitivity in tight sandstone gas reservoirs - Shaoyang Geng; Chengyong Li; Yao Li; Shuo Zhai; Tonghao Xu; Yufeng Gong; Min Jing (Gas Science and Engineering, 2023)

Knockdown of USF2 inhibits pyroptosis of podocytes and attenuates kidney injury in lupus nephritis - Ying Xie; Xiaoying Li; Wenli Deng; Nan Nan; Huimei Zou; Lei Gong; Min Chen; Jie Yu; Peilei Chen; Daolin Cui; Fan Zhang (Journal of Molecular Histology, 2023)

Selective recovery of rare earth metals from acid mine drainage by pyrrolidine diglycolamide silica column - Yiwen Wang; Yafei He; Aijun Gong; Lina Qiu; Min Zhang; Mory Traore; Xiaoning Zhan; You Li; Yuzhen Bai; Yang Liu; Ge Gao; Weiyu Zhao (Journal of Environmental Chemical Engineering, 2023)

Tuning the electronic properties of supported Cu catalysts for efficient epoxidation of long-chain α-olefins - Junze Cao; Ziyu Zhou; Min Zhang; Nengfeng Gong; Anping Yin; Yuhang Cai; Xiaodong Sun; Hongliu Wan; Yongwang Li; Zhi Cao (Fuel, 2023)

Study on international energy market and geopolitical risk contagion based on complex network - Xiao-Li Gong; Yong-Kang Feng; Jian-Min Liu; Xiong Xiong (Resources Policy, 2023)

Amine-impregnated porous carbon–silica sheets derived from vermiculite with superior adsorption capability and cyclic stability for CO2 capture - Xiaoyu Li; Ruihong Li; Kang Peng; Keping Zhao; Min Bai; Haoran Li; Weixuan Gao; Ziming Gong (Chemical Engineering Journal, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Fabrication of micro/nano spherulitic hierarchical energetic materials via noncrystallographic branching induced by polymer additives: A case study of 2,2′,4,4′,6,6′-hexanitrostilbene (HNS) - Min Li; Ying Wang; Xin Zhou; Qi Zhang; Mingyang Chen; Dandan Han; Junbo Gong; Hongzhen Li (Chemical Engineering Journal, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Reconstruction of the water cycle process reveals the 600-year evolution of the human-water relationship in Tunpu, China - Shengtian Yang; Zihao Pan; Hezhen Lou; Chaojun Li; Jun Zhang; Yujia Zhang; Yin Yi; Jiyi Gong; Ya Luo; Min Zhi; Xi Li (Journal of Hydrology, 2023)

Enhanced silicate remediation in cadmium-contaminated alkaline soil: Amorphous structure improves adsorption performance - Lulu Long; Na Huang; Xin Liu; Li Gong; Min Xu; Shirong Zhang; Chao Chen; Jun Wu; Gang Yang (Journal of Environmental Management, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Pollution characteristics and risk assessment of heavy metals in surface water of Manas River, Xinjiang, China - Shaohua He; Bingbing Tian; Fengyu Liu; Junqi Wang; Shuyi Gong; Jianjiang Lu; Min Li (Arabian Journal of Geosciences, 2022)

Risk Identification of Heavy Metals in Agricultural Soils from a Typically High Cd Geological Background Area in Upper Reaches of the Yangtze River - Xiaosong Tian; Guanqun Chai; Qing Xie; Min Fan; Song Qin; Chengwu Fan; Yalong Gong; Jinhu Liu; Guanghui Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Correction to: GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinfammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

First report of Pseudocercospora coprosmae causing leaf spot on Scaevola taccada in China - Min Li; Zhaoyin Gao; Xiqiang Song; Qing Chen; Deqiang Gong; Junxia Mu; Meijiao Hu (Journal of Plant Pathology, 2022)

LncRNA-SNHG16 promotes proliferation and migration of acute myeloid leukemia cells via PTEN/PI3K/AKT axis through suppressing CELF2 protein - Min Shi; Ruili Yang; Jing Lin; Qi Wei; Lei Chen; Weifeng Gong; Yang Li; Xiaobo Guo (Journal of Biosciences, 2021)

First report of Colletotrichum aeschynomenes causing leaf anthracnose on Ixora coccinea in China - Min Li; Shaogang Zhang; Zhaoyin Gao; Yi Wang; Wu Zhang; Deqiang Gong; Chao Zhao; Meijiao Hu (Journal of Plant Pathology, 2021)

Dibenzocyclooctadiene lignans from Artemisia sieversiana and their anti-inflammatory activities - Xu-Dong Zhou; Chao-Xi Chen; Xi-Kang Zheng; Li-Min Gong; Ke-Wu Zeng; Wei Wang; Peng-Fei Tu (Journal of Natural Medicines, 2021)

GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinflammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2021)

Iodinated Contrast Agents Reduce the Efficacy of Intravenous Recombinant Tissue-Type Plasminogen Activator in Acute Ischemic Stroke Patients: a Multicenter Cohort Study - Zhicai Chen; Chao Xu; Wansi Zhong; Xiaoxian Gong; Haitao Hu; Xuting Zhang; Yi Chen; Qingqing Li; Zhongyu Luo; Zhuojian Chen; Min Lou (Translational Stroke Research, 2021)

First report of Diaporthe limonicola causing leaf spot on Erythrina crista-galli in China - Min Li; Zhaoyin Gao; Kunkun Zhao; Yi Wang; Deqiang Gong; Chao Zhao; Meijiao Hu (Journal of Plant Pathology, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

First report of Neofusicoccum parvum causing leaf spot of Scaevola taccada in China - Min Li; Yi Wang; Deqiang Gong; Chao Zhao; Meijiao Hu (Journal of Plant Pathology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Topiramate Reverses Physiological and Behavioral Alterations by Postoperative Cognitive Dysfunction in Rat Model Through Inhibiting TNF Signaling Pathway - Wenjie Su; Min Xie; Yao Li; Xinran Gong; Jiacen Li (NeuroMolecular Medicine, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

CD8+ T cell/IL-33/ILC2 axis exacerbates the liver injury in Con A-induced hepatitis in T cell-transferred Rag2-deficient mice - Yuanyue Zhang; Chang Qi; Lingyun Li; Shuyao Hua; Fang Zheng; Feili Gong; Min Fang (Inflammation Research, 2019)

Characterization of 18S-ITS1-5.8S rDNA in eleven species in Soleidae: implications for phylogenetic analysis - Li Gong; Wei Shi; Min Yang; Xiaoyu Kong (Hydrobiologia, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Trace Element Levels in Scalp Hair of School Children in Shigatse, Tibet, an Endemic Area for Kaschin-Beck Disease (KBD) - Ya’nan Guo; Hairong Li; Linsheng Yang; Yonghua Li; Binggan Wei; Wuyi Wang; Hongqiang Gong; Min Guo; Cangjue Nima; Shengcheng Zhao; Jing Wang (Biological Trace Element Research, 2017)

Impacts of nitrogen addition on the carbon balance in a temperate semiarid grassland ecosystem - Qinpu Luo; Jirui Gong; Lili Yang; Xiaobing Li; Yan Pan; Min Liu; Zhanwei Zhai; Taoge-tao Baoyin (Biology and Fertility of Soils, 2017)

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

Isolation and Complete Genome Sequence of a Novel Pseudoalteromonas Phage PH357 from the Yangtze River Estuary - Zheng Gong; Min Wang; Qingwei Yang; Zhongshi Li; Jun Xia; Yu Gao; Yong Jiang; Xue Meng; Zhaoyang Liu; Ding Yang; Fangfei Zhang; Hongbing Shao; et al. (Current Microbiology, 2017)

Characterization and Genome Sequence of Marine Alteromonas gracilis Phage PB15 Isolated from the Yellow Sea, China - Yu Gao; Qian Liu; Min Wang; Guihua Zhao; Yong Jiang; Gill Malin; Zheng Gong; Xue Meng; Zhaoyang Liu; Tongtong Lin; Yutong Li; Hongbing Shao (Current Microbiology, 2017)

Glycyrrhizin ameliorates experimental colitis through attenuating interleukin-17-producing T cell responses via regulating antigen-presenting cells - Xiangyu Chen; Dai Fang; Lingyun Li; Liyong Chen; Qirui Li; Feili Gong; Min Fang (Immunologic Research, 2017)

Spontaneous Peripheral Ameloblastic Odontoma in a Male Sprague-Dawley Rat - Yinghua Li; Han-Ik Bae; Hak-Soo Kim; Min-Soo Kang; Bo-Ho Gong; Won-Hee Jung; Sranna Lee; Jin-Sook Bae; Kap-Ho Kim; Si-Whan Song; Jae-Hyun Lee; Boo-Hyon Kang (Toxicological Research, 2017)

p38 MAPK Participates in the Mediation of GLT-1 Up-regulation During the Induction of Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning - Min Zhang; Jian-Xue Gong; Jia-Lei Wang; Meng-Yang Jiang; Li Li; Yu-Yan Hu; Jie Qi; Ling-Yan Zhang; Hang Zhao; Xin Cui; Xiao-Hui Xian; Wen-Bin Li (Molecular Neurobiology, 2017)

Long duplication of 18S ribosomal DNA in Cynoglossus lineolatus (Pleuronectiformes: Cynoglossidae): novel molecular evidence for unequal crossing over model - Li Gong; Wei Shi; Min Yang; Lizhen Si; Xiaoyu Kong (Acta Oceanologica Sinica, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Distribution of soil carbon in different grassland types of the Qinghai-Tibetan Plateau - Shu-li Liu; Yan-gong Du; Fa-wei Zhang; Li Lin; Yi-kang Li; Xiao-wei Guo; Qian Li; Guang-min Cao (Journal of Mountain Science, 2016)

Overexpression of S-adenosylmethionine synthetase 1 enhances tomato callus tolerance to alkali stress through polyamine and hydrogen peroxide cross-linked networks - Biao Gong; Xiufeng Wang; Min Wei; Fengjuan Yang; Yan Li; Qinghua Shi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Antimicrobial activity of secondary metabolites from Streptomyces sp. K15, an endophyte in Houttuynia cordata Thunb - Huabao Chen; Chunping Yang; Tao Ke; Miaomiao Zhou; Zhaojun Li; Min Zhang; Guoshu Gong; Taiping Hou (Natural Product Research, 2015)

Effects of Graded Levels of Chromium Methionine on Performance, Carcass Traits, Meat Quality, Fatty Acid Profiles of Fat, Tissue Chromium Concentrations, and Antioxidant Status in Growing-Finishing Pigs - Yao-Yao Tian; Li-Min Gong; Jian-Xiang Xue; Jun Cao; Li-Ying Zhang (Biological Trace Element Research, 2015)

Hair Selenium Levels of School Children in Kashin–Beck Disease Endemic Areas in Tibet, China - Zhuo Chen; Hairong Li; Linsheng Yang; Wuyi Wang; Yonghua Li; Hongqiang Gong; Min Guo; Cangjue Nima; Shengcheng Zhao; Jing Wang; Bixiong Ye; Sangbu Danzeng; et al. (Biological Trace Element Research, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Population genetic structure and approximate B ayesian computation analyses reveal the southern origin and northward dispersal of the oriental fruit moth G rapholita molesta ( L epidoptera: T ortricidae) in its native range - Shu‐Jun Wei; Li‐Jun Cao; Ya‐Jun Gong; Bao‐Cai Shi; Su Wang; Fan Zhang; Xiao‐Jun Guo; Yuan‐Min Wang; Xue‐Xin Chen (Molecular Ecology, 2015)
The oriental fruit moth ( OFM ) Grapholita molesta is one of the most destructive orchard pests. Assumed to be native to China, the moth is now distributed throughout the world. However, the evolutionary history of this moth in its native range remains unknown. In this study, we explored the population genetic structure, dispersal routes and demographic history of the OFM in China and South Korea based on mitochondrial genes and microsatellite loci. The Mantel test indicated a significant correlation between genetic distance and geographical distance in the populations. Bayesian analysis of population genetic structure ( baps ) identified four nested clusters, while the geneland analysis inferred five genetic groups with spatial discontinuities. Based on the approximate Bayesian computation approach, we found that the OFM was originated from southern China near the Shilin area of Yunnan Province. The early divergence and dispersal of this moth was dated to the Penultimate glaciation of Pleistocene. Further dispersal from southern to northern region of China occurred before the last glacial maximum, while the expansion of population size in the derived populations in northern region of China occurred after the last glacial maximum. Our results indicated that the current distribution and structure of the OFM were complicatedly influenced by climatic and geological events and human activities of cultivation and wide dissemination of peach in ancient China. We provide an example on revealing the origin and dispersal history of an agricultural pest insect in its native range as well as the underlying factors.

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Vitamin A Deficiency Impairs Spatial Learning and Memory: The Mechanism of Abnormal CBP-Dependent Histone Acetylation Regulated by Retinoic Acid Receptor Alpha - Nali Hou; Lan Ren; Min Gong; Yang Bi; Yan Gu; Zhifang Dong; Youxue Liu; Jie Chen; Tingyu Li (Molecular Neurobiology, 2015)

Effects of Chromium Methionine Supplementation on Growth Performance, Serum Metabolites, Endocrine Parameters, Antioxidant Status, and Immune Traits in Growing Pigs - Yao-Yao Tian; Li-Ying Zhang; Bing Dong; Jun Cao; Jian-Xiang Xue; Li-Min Gong (Biological Trace Element Research, 2014)

Comparative effects of NaCl and NaHCO3 stresses on respiratory metabolism, antioxidant system, nutritional status, and organic acid metabolism in tomato roots - Biao Gong; Dan Wen; Sean Bloszies; Xiu Li; Min Wei; Fengjuan Yang; Qinghua Shi; Xiufeng Wang (Acta Physiologiae Plantarum, 2014)

Source apportionment and secondary organic aerosol estimation of PM2.5 in an urban atmosphere in China - XiaoFeng Huang; Hui Yun; ZhaoHeng Gong; Xiang Li; LingYan He; YuanHang Zhang; Min Hu (Science China Earth Sciences, 2014)

Molecular phylogenetic analysis of dominant microbial populations in aged refuse - Yan He; Zhihong Li; Liping Yao; You Cai Zhao; Min Sheng Huang; Gong Ming Zhou (World Journal of Microbiology and Biotechnology, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Expression of Immune Molecules CD25 and CXCL13 Correlated with Clinical Severity of Myasthenia Gravis - Min Zhang; Jun Guo; Hongzeng Li; Yongan Zhou; Feng Tian; Li Gong; Xianni Wang; Zhuyi Li; Wei Zhang (Journal of Molecular Neuroscience, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Association study of ACE polymorphisms and systemic lupus erythematosus in Northern Chinese Han population - Ai-min Gong; Xin-yuan Li; Yi-qin Wang; Hai-xia Yan; Zhao-xia Xu; Zhao Feng; Yi-qiang Xie; De-hui Yin; Shi-zhong Yang (Molecular Biology Reports, 2012)

Magnesium Deficiency Results in Damage of Nitrogen and Carbon Cross-talk of Maize and Improvement by Cerium Addition - Haiquan Zhao; Qiuping Zhou; Min Zhou; Chunxiao Li; Xiaolan Gong; Chao Liu; Chunxiang Qu; Ling Wang; Wenhui Si; Fashui Hong (Biological Trace Element Research, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

A miR-125b binding site polymorphism in bone morphogenetic protein membrane receptor type IB gene and prostate cancer risk in China - Ninghan Feng; Bin Xu; Jun Tao; Pengchao Li; Gong Cheng; Zhichao Min; Yuanyuan Mi; Meilin Wang; Na Tong; Jialin Tang; Zhengdong Zhang; Hongfei Wu; et al. (Molecular Biology Reports, 2012)

The Mechanism of Liver Injury in Mice Caused by Lanthanoids - Min Fei; Na Li; Yuguan Ze; Jie Liu; Sisi Wang; Xiuaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Oxidative Stress in the Liver of Mice Caused by Intraperitoneal Injection with Lanthanoides - Min Fei; Na Li; Yuguan Ze; Jie Liu; Xiaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Lack of association between ADRA2B -4825 gene insertion/deletion polymorphism and migraine in Chinese Han population - Jian-Qiang Ni; Sha-Sha Jia; Min Liu; Shou-Gong Chen; Yu-Ting Jiang; Wan-Li Dong; Yu-Zhen Gao (Neuroscience Bulletin, 2010)

Assessing heavy-metal contamination and sources by GIS-based approach and multivariate analysis of urban–rural topsoils in Wuhan, central China - Min Gong; Li Wu; Xiang-yang Bi; Li-min Ren; Lei Wang; Zhen-dong Ma; Zheng-yu Bao; Zhong-gen Li (Environmental Geochemistry and Health, 2010)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Gis supported hedonic model for assessing property value in west Oakland, California - De-min Zhou; Jian-chun Xu; Hui-li Gong (Chinese Geographical Science, 2006)

Antagonism of Transforming Growth Factor-Β Signaling Inhibits Fibrosis-Related Genes - Xing-Jun Liu; Cheng-Mai Ruan; Xian-Feng Gong; Xing-Zhou Li; Huai-Liang Wang; Min-Wei Wang; James Q. Yin (Biotechnology Letters, 2005)

Transactivation of RARE and GRE in the cellular response to arsenic - Chuanshu Huang; Jingxia Li; Min Ding; Max Costa; Vincent Castranova; Val Vallyathan; Gong Ju; Xianglin Shi (Molecular and Cellular Biochemistry, 2001)

Arsenic‐induced NFκβ transactivation through Erks‐ and JNKs‐dependent pathways in mouse epidermal JB6 cells - Chuanshu Huang; Jingxia Li; Min Ding; Liying Wang; Xianglin Shi; Vincent Castranova; Val Vallyathan; Gong Ju; Max Costa (Molecular and Cellular Biochemistry, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)